Impact of First-Line Therapy on Selection of Second-Line Therapy in FIRE-3 Trial - Mosley, Mary (MD Conference Express, 2014)
The influence of the drug combination used for first-line therapy on the selection and duration of the second-line therapy in patients with metastatic colorectal cancer (mCRC) was the objective of a post hoc analysis in the ongoing 5-FU, Folinic Acid and Irinotecan (FOLFIRI) Plus Cetuximab Versus FOLFIRI Plus Bevacizumab in First Line Treatment Colorectal Cancer trial [FIRE-3]. This article discusses the effect of first-line therapy on overall survival (OS) and the selection of subsequent treatment, and the effect of second-line therapy on OS [Modest D et al. Ann Oncol. 2014 (abstr O-0018)].